Impact of the Organizational Culture on the Employee’s performance Zain Telecom as a Case Study, Khartoum-Sudan - Zoltán Veres; Alfateh Fegada (European Scientific Journal, ESJ, 2022)
The study addressed the impact of organizational culture “OC” on the employee’s performance in zain telecommunication company located in Khartoum-Bahri, SDN. The study discussed the flowing main question: Does organizational culture affect the employee’s performance? The study aimed to clarify the impact of organizational culture on the employee’s performance among the dimensions of (performance improvement, and performance efficiency). Based on the literature studies, and to conduct the study with the respondent we have implemented a quantitative-descriptive analytical approach and the case study method. The questionnaire was the main tool for collecting the data. Meanwhile, 32 questionnaires have distributed to respondents. The main hypothesis of the study was, that there was a relationship between organizational culture and employee performance in Zain telecommunication company. Moreover, to confirm the reliability and validity of the questionnaire, it has distributed to (3) arbitrators, in addition to calculating the credibility and reliability coefficient of Cronbach's alpha, the value was 90%. We have utilized (SPSS) program in order to analyze the data. One of the most important findings of the study is that we have found a significant relationship between organizational culture and performance efficiency, and there is a significant relationship between organizational culture and performance improvement.